PEMBERDAYAAN WARGA DALAM PENEGAKAN HUKUM MELALUI CITIZEN JOURNALISM: PERAN DAN TANTANGAN: Empowering Citizens in Law Enforcement through Citizen Journalism: Roles and Challenges - Marzuki, Rusdi; Azwar, T. Keizerina Devi (Res Nullius Law Journal, 2024)
"Citizen journalism," or "jurnalisme warga," has become a powerful force in directing news narratives and influencing public opinion, with a notable impact on law enforcement. This article explores the pivotal role of citizen journalism in supporting law enforcement and the associated challenges. The key issues addressed include the role of citizen journalism in law enforcement and a comparative analysis of cases in Indonesia and the United States. Employing a normative legal research method with a case study approach, the study draws cases from court directories in both countries. Through qualitative analysis, it demonstrates that while citizen journalism enhances law enforcement by rapidly disseminating information, mobilizing public opinion, and documenting events firsthand, challenges exist. These challenges encompass issues of credibility, validity, lack of neutrality due to personal perspectives, and the need for source and privacy protection. The article underscores that, although citizen journalism significantly contributes to law enforcement, improvements in skills, collaboration, and regulation are essential for maximizing its positive impact. In conducting a comparative analysis between Indonesia and the United States, the study aims to identify similarities, differences, and lessons learned in each context, providing valuable insights for the future of citizen journalism in law enforcement.